Simulação da dinâmica do controle de carga: controle de entrada/saída com realimentação - Oliveira, Allan Freitas (Universidade Federal de São Carlos, 2021)
With the growing need for a fast response to the demand disturbances, dynamic models rise as an alternative to discrete events simulation, usually used on the application of Workload Control rules. However, applications of dynamic modeling tools, like dynamic control with feedbacks, to Workload Control models, are not explored on literature. Therefore, the objective of this paper is to model a Production Planning and Control Workload Control system which fills this gap – with the implementation of simultaneous input and output control – and analyze the system’s behavior up to demand perturbations. The order release policy (input control) is based upon the load of the machines downstream and also the load of the pool itself. The capacity adjustment of each machine (output control) is based on the level of the preceding buffer. Three simulations with demand/input fluctuation were carried out. The results show that the feedback control implemented leads the system to balance on simulations A and B, in which the buffer levels reach the reference levels and the processing frequencies stabilize. In Simulation C, the system responded to the cyclic demand disturbances with a maximum increase of 15% on the capacity adjustment. Furthermore, even with a 20% demand increase, the buffer levels didn’t vary significantly. This novel approach (closed loop) provides prescriptive directions for a more balanced and predictable shop floor, and also reactive to disturbances.
Simulation of the workload control dynamics: input/output control with feedback loop
Keywords: Controle de carga; Modelagem dinâmica; Controle de entrada e saída; Teoria de controle; Planejamento e controle da produção; Sistema de malha fechada; Workload control; Dynamic modeling; Input and output control; Control theory; Production planning and control; Closed-loop system; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO